PENGARUH KESADARAN PAJAK, PENERAPAN E-FILLING, DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK: STUDI EMPIRIS PADA WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KPP PRATAMA AMBON - Latuamury, Jabida; Hilewe, Christin Maya (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2024)
This study aims to analyze the impact of tax awareness, the implementation of e-filing, and tax sanctions on the tax compliance of individual taxpayers registered at KPP Pratama Ambon. Tax compliance is a crucial factor in increasing state revenue, which necessitates examining various aspects that influence it. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents, who are individual taxpayers registered at KPP Pratama Ambon. The analysis technique used is multiple linear regression to examine the effect of independent variables on the dependent variable. The findings reveal that tax awareness and the implementation of e-filing have a positive and significant effect on tax compliance, indicating that higher tax awareness and more effective e-filing systems lead to increased taxpayer compliance. However, tax sanctions do not have a significant effect on compliance. This suggests that while tax sanctions are intended to encourage compliance, taxpayers are more influenced by awareness and the ease of filing systems. These findings are expected to provide valuable insights for the government in enhancing tax policies to improve taxpayer compliance in the future.